Comparing The Efficacy of Different Antibiotic Regimens in The Treatment of Community-Acquired Pneumonia Based on Clinical Outcomes. - Sathishkumar S, Sathishkumar S; Jebastine, M. Immanuel (Journal of Neonatal Surgery, 2025)
Background: Community-acquired pneumonia is one of the most important causes for the development of morbidity and hospitalization in the world and, hence, requires timely and effective antibiotics therapy. This study was undertaken to compare the efficacy, clinical outcomes, and safety of three different antibiotic regimens in patients suffering from CAP. Methodology: This study examined the 150 patients suffering from CAP, with fifty patients per group: Regimen A, Regimen B, and Regimen C. Important parameters observed include normalization of vital signs, clinical improvement, clinical stability, time interval to clinical improvement, length of hospital stay, side effects, mortality, and thirty-day readmission rates. Data were analyzed and tested for statistical significance to show the efficacy of the different regimens. Results: All three regimens showed complete stability within 24 hours, with overall clinical improvement rates at 84.0%, with Regimen C showing the greatest improvement, followed by Regimen B (72.0%) and Regimen A (64.0%). This shows that although the three regimens have similar effectiveness on clinical improvement, for quicker symptom relief and clinical recovery, Regimen C emerges as the best in this study. Mean duration of hospital stay was also similar for all, ranging from 7–7.62 days, and statistically not significant (p > 0.00001). There was no death reported in any group. Side effects profile varied, with diarrhea being the most common adverse effect in Regimen C (21), whilst nausea was seen most commonly in Regimen A (20). Conclusion: Out of all three antibiotic regimens, the choice of regimen resulted in similar efficacy in the treatment of community-acquired pneumonia, with 100% clinical stability, no mortality, and comparable lengths of stay. Regimen C had the quickest resolution of fever but higher incidence of diarrhea, whereas Regimen A demonstrated more rapid improvement in dyspnea. In general, all the regimens were effective with minimal variation in side effects and time to resolution of various other symptoms.